"Let this winter world reveal what it will in its own time”: on the images of hospitality, reconciliation, communion and thanksgiving in Michael David O'Brien's The Father's Tale - de Oliveira Casemiro Pereira de Amorim, Victor Hugo; Martins de Paula, Ribanna (Revista X, 2024)
Based on Weisgerber (1978) and Durand (1993), we understand that symbolic language allows the unity of a literary text to be sustained. By transfiguring familiar elements for both readers and characters, it seems to bring together narrative components that are scattered throughout the artistic text. The novel to which this work is dedicated, The Father’s Tale (O’Brien, 2011), tells the saga of Alexander Graham who wanders down several tortuous paths in order to find Andrew Graham, his youngest son. During his journey, the character has a series of daydreams which, according to Amorim (2023), are particularly concerned with nostalgia for his hometown. Engendered by the poetic, dreamlike and cosmic aspects of the images of the house, the snow and the igloo, following Durand’s (1993) classification, these fantasies, as we intend to demonstrate in this article, are also linked to ideas of hospitality, reconciliation, communion and thanksgiving. Therefore, we were able to see how literary images can be combined with multiple meanings.